Electromechanical properties of iron and silver sheathed Sr0.6K0.4Fe2As2 tapes. (28th January 2015) - Kováč, P; Kopera, L; Melišek, T; Kulich, M; Hušek, I; Lin, H; Yao, C; Zhang, X; Ma, Y
Abstract: This work describes the electromechanical behaviour of iron- and silver-sheathed ex situ Sr0.6 Ka0.4 Fe2 As2 (Sr-122) tape superconductors. Free-standing Sr-122 tapes were stressed by axial tension at 4.2 K under external fields at 5–6 T, and critical currents have been simultaneously measured. An attempt to reinforce Sr-122/Ag mechanically was done by simple soldering of two stainless steel strips of 40 μ m to both sides of the tape. The obtained results are compared with the electromechanical property of MgB2 /Fe. The mechanical limits of Sr-122/Fe and Sr-122/Ag regarding possible high field applications are also discussed.